2022
DOI: 10.3390/molecules27196203
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of New VEGFR-2 Inhibitors: Design, Synthesis, Anti-Proliferative Evaluation, Docking, and MD Simulation Studies

Abstract: Four new nicotinamide-based derivatives were designed as antiangiogenic VEGFR-2 inhibitors. The congeners were synthesized possessing the pharmacophoric essential features to bind correctly with the VEGFR-2 active pocket. All members were evaluated for their cytotoxic and VEGFR-2 inhibitory potentialities. Compound 6 was the most potent showingIC50 values of 9.3 ± 0.02 and 7.8 ± 0.025 µM against HCT-116 and HepG-2 cells, respectively, and IC50 of 60.83 nM regarding VEGFR-2 enzyme inhibition. Compound 6 arreste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 48 publications
1
19
0
Order By: Relevance
“…In another modification, we thought that if we change the methylene group between the NH 2 and the carbonyl group, we might get better binding results by adding a new hydrogen bonding site (Figure 4). In continuation of our efforts to obtain new immunomodulatory [35][36][37][38][39][40][41][42][43][44] and/or anticancer agents, [45][46][47][48][49][50][51] we designed and synthesized novel thalidomide analogs that were tested in vitro against the HepG-2, HCT-116, PC3, and MCF-7 cancer cell lines. By measuring the immunomodulatory effects of the synthesized compounds in HCT-116 cells against CASP8, TNF-α, VEGF, and NF-κB P65, we conducted additional research to better understand their immunomodulatory effect.…”
Section: Minimal Requirements For Basal Binding Moietiesmentioning
confidence: 99%
“…In another modification, we thought that if we change the methylene group between the NH 2 and the carbonyl group, we might get better binding results by adding a new hydrogen bonding site (Figure 4). In continuation of our efforts to obtain new immunomodulatory [35][36][37][38][39][40][41][42][43][44] and/or anticancer agents, [45][46][47][48][49][50][51] we designed and synthesized novel thalidomide analogs that were tested in vitro against the HepG-2, HCT-116, PC3, and MCF-7 cancer cell lines. By measuring the immunomodulatory effects of the synthesized compounds in HCT-116 cells against CASP8, TNF-α, VEGF, and NF-κB P65, we conducted additional research to better understand their immunomodulatory effect.…”
Section: Minimal Requirements For Basal Binding Moietiesmentioning
confidence: 99%
“…Elaboration on the details of this experimental methodology can be found in the ESI Data section † of the research. 75 4.3.10. Toxicity studies.…”
Section: 3mentioning
confidence: 99%
“…Unfortunately, treatment with the currently FDA approved VEGFR-2 inhibitors faced several drawbacks represented in their serious adverse reactions and development of a secondary resistance. 10 There drawbacks motivated the medicinal chemists to continue searching for new small molecules aiming to overcome the adverse effects and minimize resistance. 11–14…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, treatment with the currently FDA approved VEGFR-2 inhibitors faced several drawbacks represented in their serious adverse reactions and development of a secondary resistance. 10 There drawbacks motivated the medicinal chemists to continue searching for new small molecules aiming to overcome the adverse effects and minimize resistance. [11][12][13][14] Observing the structure-activity relationship of the FDA approved VEGFR-2 inhibitors revealed that they almost shared four common features namely, (a) a heterocyclic head with minimum one nitrogen atom to occupy the hinge region of the active site, (b) a spacer to occupy gatekeeper region, (c) a hydrogen bonding moiety or a pharmacophore that makes essential H-bonds with the DFG amino acids, and (d) a hydrophobic tail that lls the receptor's allosteric site [15][16][17][18][19][20] (Fig.…”
Section: Introductionmentioning
confidence: 99%